factors FACTORS AFFECTING INTRAPERSONAL PSYCHOLOGY IN STUDENTS IN THE DIGITAL ERA - Andini Dwi Arumsari; Khasanatul Kholidyah; Riskita Catur Anggraini; Alfainah Auralia Ramdhani (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
This research examines the influence of digital factors on the intrapersonal psychology of students in the digital era, particularly the aspects of self-esteem, motivation, and emotion regulation. By using a literature review method, data was collected from relevant national and international sources (2018–2023). The analysis results show that excessive use of social media contributes to a decrease in self-esteem, high access to digital information negatively affects motivation, and positive online interactions can enhance emotion regulation if supported by an external environment. These findings are expected to assist educators and policymakers in designing effective psychological interventions in the digital era to improve student well-being.